IDENTIFIKASI DAN STRATEGI PENINGKATAN KOMODITAS UNGGULAN HORTIKULTURA PADA KELOMPOK WANITA TANI DI KOTA BOGOR - Anak Agung Eka Suwarnata; Nia Sonani; Agista Rosiana (Universitas Galuh, 2023)
Various methods have been implemented to encourage the increase of horticultural commodities, especially KWT in Bogor, such as assistance with production facilities, increasing the competence of farmers and extension officers, and post-harvest processing and marketing. Nevertheless, efforts to expand horticultural commodities still need to overcome various obstacles. Identifying strengths, weaknesses, opportunities and threats from horticultural farming activities, especially KWT in Bogor, is necessary right strategy is obtained to increase only horticultural commodities that have economic value and are highly competitive, sustainable, able to improve farmers' welfare, and in line with the economic concept of green (Green Economy). Starting from this idea, it is necessary to research the identification of superior horticultural commodities and know the strengths, weaknesses, opportunities and threats of superior horticultural commodities at KWT in Bogor so that agricultural development in Bogor is right on target. The study results showed that the commodity with the highest LQ value was the ornamental plant Aglaonema, worth 274.33. The results of the SWOT analysis obtained a strategy to increase superior commodities, namely collaboration with garden decoration services or ornamental plant lovers to introduce seller brands, as well as increase promotion through social media, exhibition meetings or events, or the aglaonema ornamental plant hobbyist community, with a QSPM value of 4.364 each and 4,236.